Dietary Effects of Replacing Carbohydrate-based Breakfast Foods with Eggs in Adults at Risk for Type 2 Diabetes (P08-044-19). (24th October 2019) - Palacios, Orsolya; Maki, Kevin; Buggia, Mary; Dicklin, Mary; Bell, Marjorie; Maki, Cathleen
Abstract: Objectives: To assess the effect of breakfast egg intake, vs. energy-matched carbohydrate (CHO)-based foods, on daily energy and select nutrient intakes in free-living adults at-risk for type 2 diabetes. Methods: Overweight or obese adults with prediabetes and/or metabolic syndrome were included in this randomized crossover study consisting of two 4-wk dietary intervention periods, separated by a ≥4 wk washout. During each intervention, subjects consumed study products containing either 2 eggs/d, 6 d/wk (12 eggs/wk) at breakfast, or energy-matched CHO-based foods. Means for energy and macronutrient contents of the study breakfast meals for both interventions were approximately 550 kcal, 31–32% energy from fat and 10.5% energy from saturated fat; protein energy was 25.9% and 12.1% for the egg and CHO meals, respectively. Subjects were instructed to incorporate the study breakfast meals into their habitual diets and maintain other lifestyle habits. Daily energy, macronutrients, fiber, cholesterol, sodium and calcium intakes were assessed by 3-d diet records at baseline and at the end of each condition. Dietary data was analyzed using the Food Processor software (v11.4). Results: Overall, 30 subjects (11 male; 19 female) with mean age of 53.5 ± 1.9 y and body mass index (BMI) of 31.9 ± 0.7 kg/m 2 provided evaluable data. Reported median daily energy intake during the egg condition was 2145 kcal, which was significantly ( P = 0.008) higher than the 1996 kcal reported during the CHO condition (see Table). Dietary analyses indicate the 149 kcal/d difference was due to intake of foods other than the study products. Despite the higher reported energy intake during the egg condition, weight change from baseline did not differ between the interventions (–0.1 and 0.2 kg, for egg and CHO conditions, respectively). Median % energy intake from CHO was significantly lower and daily sodium and cholesterol intakes significantly higher during the egg condition. Conclusions: Intake of 12 eggs/wk at breakfast, vs. energy-matched CHO foods, resulted in greater reported daily energy intake and no change in body weight. Further investigation is needed to assess the impact of egg-based breakfast meals on appetite and energy expenditure. Funding Sources: American Egg Board/Egg Nutrition Center, Park Ridge, IL. Supporting Tables, Images and/or Graphs